Catch the Gleam Mount Royal, From College to University, 1910-2009 - Baker, Donald N. (The West, 2011)
Mount Royal College began in Calgary in 1910 as a small, private residential Methodist institution offering advanced elementary and secondary schooling to students from both the city and the rural hinterland. Today, it has become a degree-granting university with over 10,000 students in credit programs and some 40,000 more in continuing education courses. A former president of Mount Royal, Baker brings to this project his skills and insight as both historian and veteran administrator, examining the challenging process of inserting new degree programs and universities into the framework of academic credibility in Canada and continually adapting to a changing social, economic, and political environment. Catch the Gleam: Mount Royal, From College to University, 1910-2009 draws on an impressive body of archival sources, oral histories, and interviews as well as sound and current scholarship on the history and theory of post-secondary education.